2020
DOI: 10.1038/s41598-020-59228-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-independent association between vitamin D deficiency and polycystic ovarian syndrome in Lahore, Pakistan

Abstract: Both vitamin D deficiency and single nucleotide polymorphisms (SNPs) in the gene encoding the vitamin D receptor (VDR) have been widely reported to associate with susceptibility to polycystic ovarian syndrome (PCOS). A case-control study was conducted to study the influence of vitamin D status and genotpye for 24 SNPs in four genes in the vitamin D pathway (VDR, DBP, CYP27B1, CYP24A1) on PCOS. Statistical analyses were conducted to identify phenotypic and genotypic factors associated with risk of pcoS and to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…VDR plays an important role in the pathogenesis of PCOS by mediating the action of Vitamin D and also affecting the insulin signaling pathways (Pittas et al, 2007). Another study investigatedthat lower vitamin D was independently associated with risk of PCOS but the genetic variationof VDR had no effect (Lone et al, 2020), whereas a recent study in a model organism has investigated the role of Vitamin D3 in the ovary in PCOS indicating reduced levels of Vitamin D3 concentration and implication in the PCOS pathogenesis (Grzesiak et al, 2021). The ndings of the VDR gene as a candidate gene that plays a role or affects PCOS pathogenesis have been contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…VDR plays an important role in the pathogenesis of PCOS by mediating the action of Vitamin D and also affecting the insulin signaling pathways (Pittas et al, 2007). Another study investigatedthat lower vitamin D was independently associated with risk of PCOS but the genetic variationof VDR had no effect (Lone et al, 2020), whereas a recent study in a model organism has investigated the role of Vitamin D3 in the ovary in PCOS indicating reduced levels of Vitamin D3 concentration and implication in the PCOS pathogenesis (Grzesiak et al, 2021). The ndings of the VDR gene as a candidate gene that plays a role or affects PCOS pathogenesis have been contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a connection between PCOS and vitamin D deficiency. There is adequate evidence in the literature to suggest that vitamin D deficiency exacerbates the risk of PCOS 31 , 33 . The fact that the connection between the two cannot be explained may be due to the complex etiology of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired VD status is an important risk factor leading to development of PCOS, anovulatory infertility and increased metabolic and hormonal abnormalities 10,11 . Observational national studies on VDD association with risk of PCOS and work of our research group on animal model highlight the need of a RCT 12,33 .…”
Section: Study Rationalementioning
confidence: 99%
“…Together, PCOS and moderate VDD may exacerbate cardiovascular and metabolic characteristics in women with PCOS 10 . In addition to global studies, a strong and independent association between VDD and risk of PCOS has been identi ed in Pakistani population 12 .…”
Section: Introductionmentioning
confidence: 99%